Effect of operating leverage and financial leverage on earnings per share - Lailatus Sa'adah; Tiara Pratiwi (Institute of Computer Science (IOCS), 2023)
This study aims to determine the partial and stimulant effect of operating leverage and financial leverage on earnings per share in food and beverage sub-sector companies listed on the IDX in 2018-2022. This type of research is quantitative associative research using panel data with financial analysis techniques, multiple regression analysis, fixed effect, random effect, hausman test, t test, F test, and coefficient of determination test with a significance of 0.05 and processed using Eviews software 10. The sample in this study used purposive sampling with certain criteria and produced a sample of 4 companies. The results of this study stated that operating leverage partially had no effect on earnings per share, while financial leverage partially had an effect on earnings per share. Operating leverage and financial leverage both simultaneously affect earning per share.